Risk Perception in Facing Post-Disaster of ‘Rob’ Flood in North Jakarta Coastal Using Social Network Approach - Heni Marta Diana Matita Putti; Andri NR Mardiah; Osmar Shalih (The Journal of Indonesia Sustainable Development Planning, 2023)
So far, globally, most studies have focused only on protecting vulnerable groups with characteristics of high risk of threat in the event of a disaster. In this study, we promoted the application of social networks analysis in the study of vulnerable groups on Rob flood where the characteristics of vulnerable groups in this study are determined by adopting social capital dimensions in disasters to map the features of vulnerable groups based on basic needs after the Rob flood occurs. This research aims to see how vulnerable groups on the coast of North Jakarta can continue their social life in facing the post-disaster of Rob floods. The results showed that most of the people of RW 22 were immigrants who had hometowns in the village. They are not worried about staying in the camp even though they risk tidal flooding because they can go home anytime if forced to.